Spontaneous expulsion of a large infarcted endometrial polyp - Brar, Rupinder K.; Deshpande, Archana H.; Gargade, Chitrawati B.; Singh, Ashok (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
A 30-year-female presented to gynaecology OPD with history of polymenorrhea for two months. Cervical scrape smear was negative for intraepithelial lesion/malignancy. The importance of sending the tissue for histopathological examination cannot be undermined considering the fact that the differential diagnosis includes malignancy.